A Novel Ratiometric Electrochemical Biosensor Based on a Split Aptamer for the Detection of Dopamine with Logic Gate Operations. Issue 13 (5th March 2020) - Guo, Ting; Wu, Changtong; Offenhäusser, Andreas; Mayer, Dirk
Abstract : A novel dual‐signal ratiometric electrochemical biosensor based on a split aptamer is developed. A common shortcoming of amperometric aptamer sensors is unspecific signaling due to ssDNA conformational flexibility. Herein, a ratiometric detection using two competitive redox‐labeled aptamer strands is proposed. The neurotransmitter dopamine (DA) is chosen as a model target due to its importance for signal processing in the central nervous system. A DA aptamer is split into two parts, S1 and S2, where strand S1 is tethered to the electrode, whereas the second strand is labeled with methylene blue (MB) and acts as a redox reporter. Another ssDNA strand (CS1) tagged with anthraquinone (AQ) is introduced, which is complementary to strand S1 and reports on surface‐tethered strands that remain in its virgin state. In the presence of DA, CS1 is released from the surface due to the formation of S1–S2–DA complexes, resulting in decreasing AQ and increasing MB Faraday currents. Furthermore, logic gate operations can be performed to either improve signal reliability or enlarge the detection range. This proof‐of‐concept study demonstrates that the splitting of a full aptamer into two parts together with the use of complementary ratiomeric tests can improve the reliability of the sensor response. Abstract : A novel dual‐signal ratiometric electrochemical biosensor based on a split aptamer is presented, which utilizes two ssDNA probes with different redox tags for the detection of dopamine. Combining both redox signals by applying AND or OR logic‐gate operations results in an improvement of the sensor reliability or enlarged detection range in comparison with a single‐signal operation.